Eosinophilia: a case series with review on different clinical presentations of eosinophilia - Patil, Supriya L.; Patil, Lalit G.; Masane, Priya N.; Agrawal, Prashant P. (International Journal of Advances in Medicine, 2017)
In this article, the term eosinophilia is defined as an increase in peripheral blood eosinophilic leukocytes to more than 500 cells per microlitre of blood. Emphasis is placed on the number of eosinophils circulating in the peripheral blood, although an increase in eosinophils can be observed in other body fluids and many body tissues. Most cases of secondary eosinophilia are treated on the basis of underlying causes. Parasitic and fungal infections can be worsened or disseminated by use of steroids and should be ruled out. In patients with primary eosinophilia without organ involvement, no treatment may be necessary. Peripheral eosinophilia does not necessarily correlate with organ involvement. Steroid responsiveness should be evaluated, both for prognosis (steroid responsive patients do better) and to guide treatment when needed. We herein present a case series of three patients of blood eosinophilia who presented to the Sudha Multispecialty Hospital and Critical Care Centre and Shri. Bhausaheb Hire Govt Medical College, Dhule during 2012- 2014. We reported three cases of eosinophilia. First patient was 22 yr. male presenting with chronic fever and cough. He was prescribed antituberculous treatment for chronic fever and cough not responding to antibiotics. PBS revealed eosinophils, serum IgE levels increased. Treated with DEC and improved. Second patient was presented with abdominal pain and severe leg pain and cramps. Ultrasound abdomen showed appendicitis. Her CBC revealed increased TLC. Surgeon has advised surgery for appendicitis. Careful examination of PBS showed eosinophilia. She was prescribed DEC (Diethylcarbamazine) for 3 weeks and her symptoms were relieved. Third patient presented with fever of unknown origin (FUO). PBS and bone marrow showed eosinophilia. Serum IgE levels increased. Treated with DEC and steroids and improved. Patients presenting with common complaints such as fever, cough, breathlessness, weakness and associated increased leukocyte count does not always have bacterial infection. Careful examination of peripheral blood smear may reveal eosinophilia. All above mentioned patients were diagnosed late because increased eosinophils were never thought as a cause of raised TLC. Awareness about peripheral eosinophilia may help in early diagnosis of such patients.